An Investigation on the Antioxidant Activity of Essential Oil of Zataria multiflora Boiss. in Soy Bean Oil - N Shahsavari; M Barzegar; MA Sahari; H Naghdi Badi (Institue of Medicinal Plants, ACECR, 2008)
Background: Great interest has recently been focused on the addition of herbs and their derivatives to foods and biological system, due to their well-known abilities to scavenge free radicals. Objective: The aims of this study were to evaluate the antioxidant activity of the essential oil of Zataria multiflora Boiss. and (ii) to use this essential oil as natural antioxidant in crude soy bean oil. Methods: In this study, essential oil was: (i) analyzed by GC/MS and its chemical components were identified. The antioxidant activity of essential oil was investigated with DPPH∙ free radical scavenging and β-carotene bleaching methods and was compared with synthetic antioxidant (BHT). Also, the antioxidant activity of essential oil was determined by measuring peroxide and thiobarbituric acid values in crude soy bean oil (oven test). Results: Results showed that carvacrol (26.08%) and thymol (17.23%) were main phenolic components in the essential oil. The EC50 value of Zataria multiflora essential oil was determined as 2.22 ± 0.04 mg/ml. This parameter for BHT was 0.58 ± 0.02. By the β-carotene bleaching system, antioxidant activity of essential oil at 0.45% was equal to 72% and for BHT at 0.1% was determined 81%. In oven test, the antioxidant activity of Zataria multiflora essential oil at 0.1% was almost equal to BHA at 0.02 % in crude soy bean oil. Conclusion: The essential oil showed good antioxidant activity and therefore, it can be used as a natural antioxidant in some foods after complementary tests.